Transurethral balloon dilation safety and efficacy in patients with recurrent bladder neck contracture after transurethral interventions - Sh. A. Abbosov; A. B. Shomarufov; D. R. Aminova (Вестник урологии, 2024)
Introduction. Currently, urologists are divided on which method is most effective for treating bladder neck contracture (BNC) after surgery: transurethral resection (TUR) or incision.Objective. The study aimed to assess the balloon dilation safety and success in patients with recurrent bladder neck contracture (BNC) after endoscopic surgery for benign prostatic hyperplasia (BPH).Materials & Methods. This study involved 110 patients with recurrent BNC after transurethral interventions for BPH. All patients underwent TUR of the bladder neck and were divided into 2 groups: group A (n = 45) included men who, after TUR, additionally underwent repeated balloon dilation, while the control group B (n = 65) included men who were treated with alpha-blockers alone.Results. In 9 months after TUR and 3 months after the fourth balloon dilation procedure in group A, the mean international prostate symptom score (IPSS) decreased from 20.1 ± 8.4 to 17.2 ± 7.4, and the IPSS-quality of life (QoL) was 4.2 ± 1.2 (p > 0.05). In group B, they were 21.7 ± 7.7 and 4.7 ± 1.1 (p > 0.05), respectively. Additionally, the mean flow rate in group A was 13.2 ± 5.4 ml/s, while in group B, it was 8.7 ± 4.9 ml/s (p < 0.05). There was a significant decrease in the post-void residual urine volume (PVR) from 76.2 ± 96.1 ml to 37.6 ± 55.1 ml in group A, whereas, in group B, it increased from 63.0 ± 36.9 ml to 79.4 ± 71.6 ml (p > 0.05). Also, 28.0% of patients of group B, and 13.3% of patients of group A underwent repeated TUR of the bladder neck in 9 months follow-up period (p < 0.05).Conclusion. Balloon dilation procedure is a relatively safe less invasive procedure and can reduce the BNC recurrence rate and consequently the rate of repeated transurethral interventions.